The n-butanol fraction of the Xiao-Chai-Hu decoction alleviates the endocrine disturbance in the liver of mice exposed to lead. (28th October 2021) - Jia, Zheng; Yang, Fan; Liu, Xiaoqing; Zhang, Xiaomeng; Hu, Wanjun; Sheng, Zunlai
Abstract: Ethnopharmacological relevance: Lead is a toxic heavy metal that causes health risks globally. However, the mechanism of endocrine poisoning and detoxification of lead poisoning, especially in the liver, still needs to be studied. Xiao-Chai-Hu decoction (XCHD) is regarded as an antidote and an anti-hepatotoxic traditional prescription that has been recorded in the pharmacopeia of the People's Republic of China. Aim of the study: The study aimed to probe the hepatoprotective activity of XCHD in the regulation of endocrine dysfunction in the liver and its molecular mechanism. Materials and methods: The mice from the Institute of Cancer Research (ICR) were exposed to different concentrations of XCHD and lead. Then, serum biochemical indices and liver pathology were analyzed. The key differential genes were detected by qRT-PCR and Western blot. Results: According to the biochemical and histopathological analysis, XCHD-NBA was the most effective in attenuating lead-induced hepatotoxicity. From the transcriptome, we analyzed the key genes of XCHD-NBA in the regulation of lead toxicity, including Tubb2a, Stip1, Cyp4a12a, Cyp2c50, Ugt1a1, Cyp3a11, Cyp4a12b, Ahsa1, Cyp2c54, Tubb4b, Esr1, Hsp90aa1, Tuba1a, Tuba1c, and Hsph1. We also analyzed the main components of XCHD-NBA by LC-MS. Because of their extensive role in regulating the endocrine function, baicalin and glycyrrhizin were identified as the main active components of XCHD in regulating endocrine disorders caused by lead. Conclusions: Lead can disturb the endocrine regulatory process of the liver, while XCHD-NBA alleviates lead-induced liver injury by regulating the endocrine regulatory process. Graphical abstract: Image 1 Highlights: Transcriptome analysis revealed the endocrine pathway which lead disturb. The n-butanol phase of Xiao-Chai-Hu decoction can reduce the endocrine disturbance caused by lead. The main components of n-butanol phase of Xiao-Chai-Hu decoction were identified by LC-MS.